Performance matters: students' perceptions of Artificial Intelligence Coach adoption factors. Issue 1 (2nd January 2023) - Terblanche, Nicky; Molyn, Joanna; Williams, Kevin; Maritz, Jeanette
ABSTRACT: The rise of AI coaching could significantly reduce cost and increase the scale of coaching, however for AI coaching to succeed it is important to understand factors that promote or inhibit adoption. Students are a particular population who may benefit from coaching but cannot afford a human coach. This qualitative study investigated the perceptions of university students on factors that could influence their use of an AI chatbot coach. Students ( n = 11) used an AI coach for 12 weeks as part of weekly group coaching workshops. They were subsequently interviewed and AI coach experience analysed deductively using the Unified Theory of Acceptance and Use of Technology framework. Findings reveal that students' positive attitude and performance expectations played an important role in their chatbot engagement. Students perceived the AI coach as accessible, easy to use, intelligent and quick to respond. They perceived the AI coach to pose minimal threat and would use it more if their friends did. The technology platform and information about accessing the AI coach was also deemed important. These findings are significant in helping creators of AI coaching technology and educational institutions, who purchase such services, to understand which aspects influence students' decision to use an AI coach.